ANALISIS PENGARUH INTEGRITY LEADERSHIP DAN PENGEMBANGAN KARIR TERHADAP MOTIVASI INTRINSIK DAN KINERJA KARYAWAN PADA PT. ASURANSI JASA INDONESIA CABANG RIAU - Prihasianto, Fajar; Hendriani, Susi; Garnasih, Raden Lestari (Komunitas Manajemen Kompetitif, 2023)
ABSTRACT. Fajar Prihasianto, NIM 2010241802. Analysis of the Effect of Integrity Leadership and Career Development on Intrinsic Motivation and Employee Performance at PT. Asuransi Jasa Indonesia, Riau Branch. Under the guidance of Susi Hendriani and Raden Lestari Garnasih. This study aims to determine the effect of Integrity Leadership and Career Development on Intrinsic Motivation and Employee Performance at PT. Asuransi Jasa Indonesia, Riau Branch. This study uses primary data, namely data obtained from the results of questionnaires to employees of PT. Asuransi Jasa Indonesia, Riau Branch. Secondary data from the company such as the general description of the company and the number of employees. The sample in this study amounted to 117 people. The sampling technique is a census or saturated sample. The analytical method used is Path Analysis with the help of the SPSS program. The results showed that 1) integrity leadership has a positive and significant effect on intrinsic motivation, 2) career development has a positive and significant effect on intrinsic motivation, 3) integrity leadership has a positive and significant effect on performance, 4) career development has a positive and significant effect on performance, 5) intrinsic motivation has a positive and significant effect on performance, 6) integrity leadership influences performance through motivation, and 7) career development influences performance through motivation. Keywords : Performance, Intrinsic Motivation, Leadership Integrity and Career Development